Color atlas of forensic pathology - Jay Dix
Time of death and decomposition. Indentification. Blunt trauma. Sudden natural death. Firearms. Shotgn injuries. Asphyxia. Thermal injuries. Electrocution, drugs and the environment. Cutting and stabbing. Motor vehicle injuries. Pediatric forensic pathology. Pediatric phatology cases.